2018
DOI: 10.1016/j.humpath.2017.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ALCAM (CD166) and PD-L1 (CD274) independently predicts shorter survival in malignant pleural mesothelioma

Abstract: Diffuse malignant mesothelioma of the pleura is a highly aggressive tumor typically associated with short survival. ALCAM (CD166), a type I transmembrane protein, is a member of the immunoglobulin superfamily. In normal cells, ALCAM regulates physiological processes such as angiogenesis and immune response. In cancer, it is associated with neoplastic progression, including invasion, migration, and metastasis. Furthermore, ALCAM is considered one of the cancer stem cell markers such as ALDH1 (ALDH1A1) and SALL4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Results from the current retrospective longitudinal study suggest that PD-L1 expression is associated with shorter OS after first-line SOC therapy (nonimmunotherapy) across a range of tumors (unadjusted HR: 1.39 [95% CI: 1.07–1.81]; p = 0.0136). Consistent with our findings, previous studies have identified an association of PD-L1 expression with shorter OS in patients with malignant salivary gland tumor [ 31 ], malignant pleural mesothelioma [ 32 ], NSCLC [ 30 , 33 ] and pancreatic cancer [ 30 , 34 ]. In contrast, other studies have reported that PD-L1 expression was associated with longer OS in patients with NSCLC [ 35 ] and SCLC [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…Results from the current retrospective longitudinal study suggest that PD-L1 expression is associated with shorter OS after first-line SOC therapy (nonimmunotherapy) across a range of tumors (unadjusted HR: 1.39 [95% CI: 1.07–1.81]; p = 0.0136). Consistent with our findings, previous studies have identified an association of PD-L1 expression with shorter OS in patients with malignant salivary gland tumor [ 31 ], malignant pleural mesothelioma [ 32 ], NSCLC [ 30 , 33 ] and pancreatic cancer [ 30 , 34 ]. In contrast, other studies have reported that PD-L1 expression was associated with longer OS in patients with NSCLC [ 35 ] and SCLC [ 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…The composition of TME holds therapeutic and prognostic implications [ 6 , 7 ]. Stage and histology are currently accepted prognostic indicators [ 5 ], but evidence is accumulation that infiltrating immune cells and expression of immune checkpoints are of high prognostic value in MPM [ 7 , 50 , 51 , 52 , 53 ]. Infiltration of M2 macrophages seems to be associated with worse prognoses [ 18 , 19 , 20 ], as is PD-L1 expression [ 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stage and histology are currently accepted prognostic indicators [ 5 ], but evidence is accumulation that infiltrating immune cells and expression of immune checkpoints are of high prognostic value in MPM [ 7 , 50 , 51 , 52 , 53 ]. Infiltration of M2 macrophages seems to be associated with worse prognoses [ 18 , 19 , 20 ], as is PD-L1 expression [ 50 , 51 , 52 , 53 ]. Infiltration of cytotoxic T cells was associated with better prognosis in MPM in most studies [ 21 , 33 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule is a vital factor not only for cell survival, motility, and cell growth but also for invasion during tumor progression and metastases. 7,8 CD166 is a glycoprotein that was initially discovered as an MHC-I for the cell surface receptor of T lymphocyte (CD6). 9 It contributes to 1) heterotypic adhesion to the lymphocyte cell-surface receptor (CD6) 10 and 2) homotypic adhesion.…”
Section: Introductionmentioning
confidence: 99%